STUDENTS’ PROBLEMS IN PUBLIC SPEAKING - Zuhra Zuhra (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
The researcher writes this research to describe the students’ problem in public speaking especially students at KPI Class of UIN Datokarama Palu in the Academic Year of 2021/2022. The design of this research was descriptive qualitative research. The researcher made the transcript of video as the source of the data. The researcher used documentation to select the data, and it was also intended to give some contributions concerning to the factors that influence the students’ problem in public speaking. The researcher had chosen the fifth semester students of KPI at UIN Datokarama Palu, in the academic year 2021/2022. The subject were 40 students. The data were analyzed by using error analysis method. The factors that influenced the problems were found out from the result of the observation and interview. The result of this research showed that many problems in public speaking was as follow; (1) Eye contact does not focus on the camera (2) They did not convey the moral message of the content (3) They did not give the reasons related to the themes discussed (4) They got too many pauses while speaking (5) The video is too short (6) They did not greet the audience (7) The video display is less attractive (8) The Sound is not clear (9) They still read the material while speaking (10) There were no gestures while they are explaining the materials (11) Their sound was covered by the back sound of the music. Where the factors influenced their problems in speaking consist of two factors; internal and external factors.From the result above, the researcher concludes that there should be a new method, strategy, and technique used by the lecturer in Public Speaking Class, so that their public speaking skill could be improved.